Foreign Direct Investment in India modelled on Globerman & Shapiro Model - Jain, Aman (2008)
India one of the emerging giants of the world, growing at almost 9% per year. This paper starts with being historical view on government's policy towards investment and then particularly towards its foreign investment. But the main objective of this paper is to test the applicability of the Globerman & Shapiro's FDI model in India. Further we give account of the impact of the pricnciple factors of this model to FDI in India and various countries.